Nanodiamond seeding on plasma-treated tantalum thin films and the role of surface contamination - Pobedinskas, P.; Degutis, G.; Dexters, W.; D’Haen, J.; Van Bael, M.K.; Haenen, K. (Applied surface science, 2021)
[Display omitted] •Electrostatic double-layer dominates in Ta surface-nanodiamond particle interaction.•Explaining the surface contamination impact on particle–surface interaction.•High nanodiamond nucleation achieved on hydrophilic and hydrophobic Ta surfaces. The surface of tantalum (Ta) thin films is exposed to different gas discharge plasmas (N2, O2, CF4) followed by an investigation of surface wetting properties and water-based colloidal seeding of ultra-dispersed nanodiamond (ND) particles. Fluorination of the Ta surface resulted in a hydrophobic surface, whereas other surface treatments resulted in hydrophilic surfaces. Regardless of treatment and wetting contact angle, the ND seeding density of approximately 2 × 1011cm−2 is obtained for all the samples. This shows that the electrostatic interaction of the Ta surface with ND particles is the primary factor determining the successful ND seeding, while the surface wetting property is of lesser importance. In addition, Ta surface contamination dynamics and its impact on ND seeding is studied. An analytic model is proposed to account for surface contamination and explain its impact on the ND seeding density. The model can be more generally applied for other material systems.